PUBLIC PERCEPTION OF THE TRADITION OF THE RITUAL OF REJECTING THE BALA BEFORE PLANTING RICE IN PASIR TINGGI VILLAGE, SOUTH TEUPAH DISTRICT, SIMEULUE REGENCY: Persepsi Masyarakat Terhadap Tradisi Ritual Tolak Bala Sebelum Tanam Padi Di Desa Pasir Tinggi Kecamatan Teupah Selatan Kabupaten Simeulue - Elis Mariana; Sri Mawaddah; Muhammad Yusuf (SOSIOEDUKASI, 2025)
This study aims to describe the community's perception of the tradition of the ritual of rejecting reinforcements carried out before the rice planting season in Pasir Tinggi Village, South Teupah District, Simeulue Regency. This tradition is an ancestral cultural heritage that is carried out from generation to generation as a spiritual effort to seek protection from pest disturbances and harm to rice plants. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that there are differences of views among the community. Most people still maintain this ritual because it is considered part of the cultural identity and local wisdom that has magical and religious value. However, some other people consider that this practice deviates from Islamic teachings because it involves giving offerings to supernatural beings which are considered a form of shirk. These findings reflect the existence of socio-religious dynamics in societies that live in the midst of the intersection between local traditions and religious teachings. This research is expected to contribute to the study of religious anthropology and the preservation of local culture.